1990
DOI: 10.1590/s0037-86821990000300002
|View full text |Cite
|
Sign up to set email alerts
|

Evolução da cardiopatia chagásica crônica humana no sertão do Estado da Paraíba, Brasil, no período de 4,5 anos

Abstract: Two sectional studies about chronic Chagas' disease were performed at a 4.5 year interval, involving the urban populations of Agua Branca, Catingueira, Emas, Imaculada, Mãe D'Agua, Olho D'Agua, Piancó and São José de Caiana counties in the Sertão region of the State of Paraíba. The evolution of heart disease was evaluated in 125 matched pairs of chronic chagasic and non-chagasic patients of the same sex, age and county of origin through electrocardiograms (ECG) at rest. The following evaluation criteria were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Females predominated in both groups (60 and 80 % group A and B, respectively) due to the greater attendance of women in clinical controls for Chagas disease, while their husbands were working and the greater willingness of women from endemic zones to transfer to the Metropolitan Region to perform cardiac Echo-Doppler. No association between sex and cardiopathy was observed; similar results were obtained by other investigators (Pereira et al 1990 ; Silva et al 2007 ), but are discordant with Basquiera et al ( 2003 ), who reported more males with Chagas cardiomyopathy.…”
Section: Discussionsupporting
confidence: 85%
“…Females predominated in both groups (60 and 80 % group A and B, respectively) due to the greater attendance of women in clinical controls for Chagas disease, while their husbands were working and the greater willingness of women from endemic zones to transfer to the Metropolitan Region to perform cardiac Echo-Doppler. No association between sex and cardiopathy was observed; similar results were obtained by other investigators (Pereira et al 1990 ; Silva et al 2007 ), but are discordant with Basquiera et al ( 2003 ), who reported more males with Chagas cardiomyopathy.…”
Section: Discussionsupporting
confidence: 85%
“…However, they were mostly migrants from 19 endemic Brazilian states, mainly Bahia and Minas Gerais. These states present the highest prevalence of CD and CHD [31], which may be the result of the varying pathogenic degrees of T. cruzi [15]. Regional differences are associated with both disease severity and the predominance of clinical forms due to factors linked to the parasitized individual (immune status, nutritional status, genetic factors, and physical effort) and to other factors related to the parasite (different strains of T. cruzi, parasitism intensity, and reinfections) [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The few prospective studies that addressed this issue considerably differed in the study population age, number of cases, length of follow-up, geographical area, living in endemic area with or without active vectorial transmission, and migration to urban areas. More recent studies using methods similar to those of the present study were conducted in different countries (Brazil, Argentina, and Venezuela) with different geographic, climatic, and ecosystem configurations and with different vector transmission dynamics, which may explain the differences in the reported rates of disease progression [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three studies 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 had longitudinal observational outcomes for patients with the indeterminate chronic form of Chagas disease ( Table 1 ). Most of these studies were of prospective cohorts and were conducted in either Brazil or Argentina between 1960 and 2005.…”
Section: Resultsmentioning
confidence: 99%